Quand les politiques environnementales attisent les tensions interculturelles en Guyane française - Théo Jacob; Marianne Palisse; Catherine Aubertin (Cahiers des Amériques Latines)
This paper shows, from three perspectives, how the environmental policies in French Guiana, trying to deal with the local cultural diversity, tend to ethnicize social relations. The Guiana Amazonian Park, which seems to be a reaffirmation of the state’s presence in the southern French Guiana, experiments modes of governance which increase inter-ethnic competition. The implementation of the Nagoya Protocol on Access to Genetic Resources and the Fair and Equitable Sharing of Benefits Arising from their Utilization has introduced a difference between different categories of the population : some of them must be consulted whereas the others mustn’t. Finally, people from immigration are a blind-spot of these policies. Migrants do not have any facility to access to the resources of the land, and are not considered as biodiversity knowledge holders.